Influence of the procurement regulatory framework on the implementation of Supply Chain Management ethics in Government Ministries in Kenya - Kinoti, Justus B.; Arasa, Robert; Waititu, Gichuhi A.; Guyo, Wario (My University, 2013)
The influence of procurement legal framework on the implementation of supply chain management ethics in Kenyan government ministries remains a key problem to date.The purpose of this study was therefore to determine the influence of the procurement legal framework on the implementation of supply chain management ethics in government ministries in Kenya.The study employed a descriptive and correlational survey research designs.The study applied a multistage sampling technique to select the sample size 144 respondents from 21ministries.Descriptive statistics was used aided by Statistical Package for Social Scientists(SPSS) to analyze the quantitative data. The study utilized descriptive and multiple regression analysis to determine the relationship between procurement legal framework and implementation of supply chain management ethics in government ministries.The study results were that the major regulatory framework issues that affect implementation of supply chain management ethics includes; low level of procurement regulations awareness, lack of enforcement of the implementation of procurement regulations, poor monitoring of how government ministries implement procurement procedures, lack of increased efficiency, transparency and accountability in the execution of supply chain management ethics and lack of effective procurement policies in the ministries.The study recommendation were that the government should promote the level of procurement regulations awareness, enforce implementation of procurement regulations,monitor how government ministries implement procurement procedures and apply internal control systems that leads to increased efficiency, transparency and accountability in the execution of supply chain management ethics.
Keywords: rocurement RegulatoryFramework; Supply Chain Management Ethics